Polymorphisms in voltage-gated sodium channel gene and susceptibility of Aedes albopictus to insecticides in three districts of northern West Bengal, India. - Moytrey Chatterjee; Sudeep Ballav; Ardhendu K Maji; Nandita Basu; Biplab Chandra Sarkar; Pabitra Saha (Public Library of Science (PLoS), 2018)
BACKGROUND:The control and prevention of dengue largely depends on vector control measures, environmental management, and personal protection. Dengue control programmes are facing great challenges due to development of insecticide resistance among vector mosquitoes. Information on susceptibility status to different insecticides is important for national programmes to formulate vector control strategies. METHODS:We have studied the larval susceptibility of Aedes albopictus to temephos and adult susceptibility to 4% DDT, 0.05% deltamethrin, and 5% malathion as per WHO protocols in the northern districts of West Bengal. Polymorphisms in the VGSC gene were studied by direct sequencing of PCR products. RESULTS:The Ae. albopictus larval population showed sensitive [Resistance Ratio (RR99)<3] to moderate levels of resistance (5<RR99>10) to temephos at different study sites. Adult bioassay results revealed that Ae. albopictus was highly resistant to DDT [Corrected Mortality (CM) < 90%] in all the study sites and susceptible to deltamethrin and malathion (CM > 98%), except in Dhupguri where a low level of resistance to deltamethrin (CM = 96.25%) was recorded. None of the six important kdr mutations (S953P, I975M/V, L978, V980G, F1474C, D1703Y) were found in the VGSC of studied mosquitoes, but we identified 11 synonymous and 1 non-synonymous mutation in the VGSC gene. CONCLUSION:The higher susceptibility level to deltamethrin and malathion, along with the absence of important kdr mutations indicates that these two insecticides are still effective against Ae. albopictus in the study areas. The susceptibility status of temephos should be monitored closely as low to moderate levels of resistance were observed in few sites. A similar study is recommended for monitoring and early detection of insecticide resistance in other parts of the country.